Child labor and health: a systematic literature review of the impacts of child labor on child's health in low- and middle-income countries. (2nd February 2018) - Ibrahim, Abdalla; Abdalla, Salma M; Jafer, Mohammed; Abdelgadir, Jihad; de Vries, Nanne
Abstract: Objective: To summarize current evidence on the impacts of child labor on physical and mental health. Methods: We searched PubMed and ScienceDirect for studies that included participants aged 18 years or less, conducted in low- and middle-income countries (LMICs), and reported quantitative data. Two independent reviewers conducted data extraction and assessment of study quality. Results: A total of 25 studies were identified, the majority of which were cross-sectional. Child labor was found to be associated with a number of adverse health outcomes, including but not limited to poor growth, malnutrition, higher incidence of infectious and system-specific diseases, behavioral and emotional disorders, and decreased coping efficacy. Quality of included studies was rated as fair to good. Conclusion and recommendations: Child labor remains a major public health concern in LMICs, being associated with adverse physical and mental health outcomes. Current efforts against child labor need to be revisited, at least in LMICs. Further studies following a longitudinal design, and using common methods to assess the health impact of child labor in different country contexts would inform policy making.